The Hudoq Kita': A Contemporary Reinterpretation of Dayak Kenyah Cosmology in Light of Islamic Legal and Theological Perspectives - Tri Indrahastuti; Trisakti; Arif Hidajad; Setyo Yanuartuti; Rina Martiara (MILRev: Metro Islamic Law Review, 2026)
This study aims to reinterpret the cosmology of the Hudoq Kita' Dance as an embodied theology within the lived experience of the Dayak Kenyah community, while also examining its relevance from the perspectives of Islamic law and theology in the contemporary era. To date, the Hudoq Kita' Dance has generally been understood as a symbolic–cultural ritual, whereas its theological and normative dimensions—particularly in dialogue with Islamic tradition—have received limited systematic scholarly attention. Employing a qualitative methodology, this research adopts ethnographic and normative–theological approaches. Data were collected through literature review, visual documentation analysis, and symbolic interpretation of movement patterns, masks, and ritual structures in the Hudoq Kita' Dance. The analysis integrates Dayak Kenyah cosmology with Islamic theological frameworks, particularly concepts regarding the relationships among humans and God, nature, and the social community. The findings indicate that the Hudoq Kita' Dance represents a cosmological worldview that emphasizes ecological harmony, collective responsibility, and spiritual consciousness as foundational elements of social life. These values resonate with the principles of tawḥīd rubūbiyyah, the concept of khalīfah fī al-arḍ, and environmental ethics within Islamic theology. From the perspective of Islamic law, the practice of the Hudoq Kita' Dance may be understood as an expression of local wisdom that does not contradict the objectives of Islamic law (maqāṣid al-sharīʿah), provided that it is interpreted symbolically and contextually and does not involve elements of shirk or violations of fundamental creedal principles. The significance of this study lies in its contribution to expanding culturally grounded scholarship in Islamic law and theology, strengthening dialogical approaches between Islam and indigenous traditions, and offering a conceptual framework for the development of an inclusive, contextually grounded cultural fiqh in Indonesia.